KONSEP PENDIDIKAN MENURUT AL-GHAZALI - Sukirman, Sukirman; Baiti, Masnun; Syarnubi, Syarnubi; Fauzi, Muhamad (PAI RAFAH, 2023)
Education is an effort made by someone so that there is a change towards the better. In Indonesia, education is more defined as a formal institution that has the aim of developing the academic potential of students in order to realize educational goals. One of the Islamic education figures is Al-Ghazali. Al-Ghazali is one of the Islamic education figures who contributed thoughts to education. Al-Ghazali since his childhood was known as a child lover of knowledge and enthusiast in search of the ultimate truth, even though he was hit by grief, hit by various forms of grief and misery. Al-Ghazali's view of education is the process of humanizing humans. While the purpose of education according to him consists of long-term and short-term goals. As an educator must be capable, not only as a teacher but also teach character education and the importance of character education for students is to become competent and noble students. Islamic religious education is one of the breakthroughs as an effort to support student character education so that the morals of all students become more noble. Morals is an attitude that is rooted in the soul from which various actions are born easily and easily, without the need for thought and consideration. If this attitude is born from good and praiseworthy actions, both in terms of reason and Shara', then it is called good morals. And if what is born from it is a despicable act, then the attitude is called bad morals. The success of an educator is to be an example and make students or learners have noble morals.